Biosystematic Studies in Annonaceae I. Vegetative and Floral Morphological Studies of Some Species of Annona in Nigeria - Folorunso, A. E.; Olorode, O. (2014)
A morphological study of four species of Annona found in Nigeria and characterized as important under-utilized species was conducted in search of intrageneric characters which may be of taxonomic value in the identification and classification of the genus. Life plants, fruits, flowers and seeds were studied form mature plants in the experimental garden. Both qualitative and quantitative characters were recorded. Additional morphological characters of taxonomic value are eucamptodromous venation, inflated petiole, chasmogamous flower and distichous phyllotaxy.